Establishment and characterization of an inflammatory cartilaginous organoids model for organoid transplantation study - Yanchao Zhang; Qing Fang; Yue Peng; Honglin Liu; Jiancheng Tang; Ruichen Ma; Weiguo Wang (Journal of Orthopaedic Translation)
Background: Transplantation of cartilaginous organoids for repairing cartilage defects in osteoarthritis represents a novel treatment approach. However, A controversial argument remains about whether cartilaginous organoids derived from the differentiation of bone marrow mesenchymal stem cells (BMSCs) in the three-dimensional (3D) environment are strictly organoids and whether the inflammatory microenvironment would affect the success rate of organoid transplantation. This study characterized 3D BMSC-derived cartilaginous organoids and developed an inflammatory organoid model to better understand the transcriptomic changes in the organoids induced by the microenvironment when transplanted into the knee with osteoarthritis. Methods: Spatial growth BMSCs were generated and cultured in the cartilage differentiation medium to establish cartilaginous organoids. The model was characterized in both morphology and biology aspects. Subsequently, IL-1β induced inflammatory cartilaginous organoids were established and the transcriptomic sequencing was performed to investigate gene expression changes. Results: BMSC-derived cartilaginous organoids were characterized by histology and immunofluorescence. Both Alcian blue and Safranin O staining revealed abundant articular cartilage extracellular matrix (ECM) in the organoids. The expression of cartilage specific ACAN and Col2A1 was confirmed by immunofluorescence. The organoids had the biological ability to repair cartilage defects. IL-1β induced inflammatory cartilaginous organoids were established and mRNA sequencing revealed downregulation of pathways related to cell adhesion and extracellular matrix organization. Upregulation of IL-6, TNF-α, CCL2 and CXCL1 was confirmed. Conclusion: We thoroughly validated and characterized BMSC-derived cartilaginous organoids and established the inflammatory cartilaginous organoid models. This study revealed that the attenuation in cell adhesion and ECM formation of organoids induced by inflammatory chemokines may decrease the success rate and effectiveness of organoids auto-transplantation for fixing cartilage defects in the inflammatory microenvironment of the OA joint. The translational potential of this article: By establishing and validating an in vitro inflammatory cartilaginous organoid model, this study provides a robust platform to examine how inflammatory mediators influence cartilage-like constructs. These findings enable the identification of targeted interventions to enhance the organoids’ resilience against the inflammatory environment commonly found in osteoarthritic joints. Ultimately, this strategy offers a novel avenue for improving transplant success and promoting cartilage defect repair in patients with OA, thereby contributing valuable insights and potential clinical applications in regenerative medicine.